Metabolic and Ruminal Fluid Markers of Dairy Cows Supplemented with a Combination of Yeast Culture and Hydrolyzed Yeast - Mumbach, Tatiele; Raimondo, Raquel Fraga e Silva; Demarco, Claudia Faccio; Freitas, Vanessa Oliveira; Grazziotin, Rodrigo Chaves Barcellos; Maffi, Andressa Stein; Gonçalves, Fernanda Medeiros; Brauner, Cassio Cassal; Jacometo, Carolina Bespalhok; Corrêa, Marcio Nunes (Acta Scientiae Veterinariae, 2017)
Background: In order to reduce the effects of a negative energy balance, some measures have been taken into account in nutritional management during the transition period. The use of yeast, has been a good alternative used to improve the rumen metabolism and helping the adjustment of the microbiotato the new diet. The aim of the study was to evaluate the effects of supplementing a combination of yeast culture and hydrolyzed yeast on the metabolism of dairy cows during the transition period. Materials, Methods & Results: The experiment was conducted in a semi-extensive system, using 20 Holstein cows, divided equally into a control group (CG) and a supplemented group (SG). The SG received 28 g/animal/day of a combination of yeast culture and hydrolyzed yeast from 20 ± 2 days pre-calving until early lactation (18 ± 3 days). Serum concentrations of non-esterified fatty acids (NEFA), albumin and urea were determined at calving, and for three time points during the early postpartum period and three time points during the early lactation period. Regarding energy metabolism, prepartum concentrations of NEFA were higher than the physiological standard in both groups. However, NEFA, albumin and urea decreased during the early postpartum period in the supplemented animals and could be attributed to the yeast in enhancing ruminal microorganisms’ cellulolytic capacity, increasing fibre digestibility and starch utilization. Discussion: The increased concentration of non-esterified fatty acids (NEFA) due to the mobilization of fat deposits that happens in the transition period, especially in the postpartum period reflects the cow’s adaptation to the negative energy balance (NEB). The lower concentrations of NEFA observed in the present study could be attributed to the effect of the yeast in enhancing the ruminal microorganisms’ cellulolytic capacity. The control cows had a BCS within the recommended range while the supplemented group had it close to the minimal limit proposed for this period. Thus, supplemented cows lost less BCS during the early postpartum period, had a lower BCS loss during the experimental period and had lower NEFA concentration that the CG. It was possible to observe a difference in serum albumin and urea between treatments only in the postpartum period. Besides showing no significant effect in BCS on prepartum period, control cows had a BCS within the recommended range while the supplemented group had it close to the minimal limit proposed for this period. Cows with high BCS prepartum had higher plasma NEFA before and after calving. It can be observed in the present study in both groups. However, a positive effect in prevent subclinical disorders might be attributed to YC, since the SG showed low NEFA plasma levels compared to the CG. Thus, supplemented cows lost less BCS during the early postpartum period, had a lower BCS loss during the experimental period and had lower NEFA concentration that the CG. There is a negative correlation between BCS and NEFA in the early postpartum period and this information explains the results observed in the present study where BCS declines in the SG are followed by a NEFA increase. This is not so marked in the CG, indicating that SG supplementation can act by improving digestibility. Yeast supplementation promotes higher output energy, enhancing postpartum performance in dairy cows. Yeast supplementation showed benefits in early lactation compared to the prepartum and early postpartum periods, suggesting that supplementation has to have an adaptation period to be effective in protein synthesis. In conclusion, supplementation with a combination of yeast culture and hydrolyzed yeast to cows during the transition period can positively influence the energy and protein metabolism, reducing the collateral effects of negative energy balance.